Kesejahteraan Psikologis pada Pasien Diabetes Mellitus Tipe 2 di Puskesmas Mulyorejo Surabaya - Rr Dian Tristiana; Kusnanto Kusnanto; Ika Yuni Widyawati; Ah Yusuf; Rizky Fitryasari (Universitas Airlangga, 2016)
Introduction: Living with chronic diseases such as Diabetes mellitus type 2 will make patients experience change or imbalance include biological, psychological, social and spiritual. One of psychology aspects in patients with Diabetes mellitus type 2 is psychological well being (PWB). Emotional response of type 2 DM patients since the early diagnosis to begin undergoing the treatment will be different for each person. Type 2 DM patients need a good transition process to achieve well being state. The transition from a healthy to a diseased condition is needed for the successful self care management of type 2 DM patients. The purpose of this research was to explore the description of PWB in patients of type 2 Diabetes mellitus in six aspects of PWB and PWB facilitate and inhibitor factors in type 2 DM patients.Methods: This research used qualitative design research with case studies approach. The subject of research was seven participants who met the inclusion criteria. Data collection was done by structured interview and observation. Data analysis was done by thematic analysis.Result and Analysis: This study generated 14 themes. The result showed that the process of type 2 DM patients subjected to the process of transition from a healthy condition into ill condition. The transition process started with cyclic lose response which influence type 2 DM patient to self control and make a right decision-making to self care. Self-control would make type 2 DM patients able to adapt and engage with new experiences that become a new habit for type 2 DM patients and will facilitate type 2 DM patients in adapting to the internal and external environment and make type 2 DM patients have a positive hope in their life.Conclusion: finding in this study would hopefully be beneficial for professional health staff to make assessment about PWB in type 2 DM patients, nurse hopefully can assist patients in transition with the condition of type 2 DM. Need further research about the relation between self acceptance and self control, activation process till engagement to new habit in type 2 DM patients, perceived support to PWB in type 2 DM patient DM.